Through Life Capability Management Perspective for Framework Development for Assessing and Measuring System Maturity, System Readiness and Capability Readiness using Architecture Frameworks - Tetlay, Abideen (IEEE, 2010)
This study investigates the use of Through Life Capability Management perspective for refinement of the Conceptual Framework for Assessing and Measuring System Maturity, System Readiness and Capability Readiness using Architecture Frameworks. Metrics and measurement frameworks have no meaning if they are not used to make decisions. The importance of decision making at the architectural level is therefore discussed which is particularly pertinent for System Maturity.
Keywords: Through Life Capability Management; Framework Assessment; System Maturity; System Readiness; Capability Readiness; Architecture Framework